1994
DOI: 10.1161/01.cir.89.4.1725
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intravascular ultrasound and angiography in the assessment of myocardial bridging.

Abstract: Intravascular ultrasound demonstrated a characteristic systolic compression of the bridge segments. The delayed compression release may explain the characteristic sharp early diastolic peak in coronary flow velocity found with intracoronary Doppler in vessels with myocardial bridging. Reduced coronary flow reserve may be related to this phenomenon, possibly explaining signs of ischemia detected in some of the patients, but may alternatively be a result of the presence of atherosclerosis in the segment proximal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
196
0
19

Year Published

1997
1997
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(220 citation statements)
references
References 23 publications
5
196
0
19
Order By: Relevance
“…Ramos et al also observed a greater severity of atherosclerosis in the proximal segment of the myocardial bridging in comparison with other affected areas at autopsy. Moreover, Ge et al performed intravascular ultrasound in 14 patients with angiographic evidence of myocardial bridging in the left anterior descending artery (12). They reported that no atherosclerotic lesions were detected in the myocardial bridging or the distal segment in the 8 patients in whom the intravascular ultrasound catheter was successfully advanced through the entire myocardial bridging, but atherosclerotic plaques were found in the proximal segment in 12 of 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…Ramos et al also observed a greater severity of atherosclerosis in the proximal segment of the myocardial bridging in comparison with other affected areas at autopsy. Moreover, Ge et al performed intravascular ultrasound in 14 patients with angiographic evidence of myocardial bridging in the left anterior descending artery (12). They reported that no atherosclerotic lesions were detected in the myocardial bridging or the distal segment in the 8 patients in whom the intravascular ultrasound catheter was successfully advanced through the entire myocardial bridging, but atherosclerotic plaques were found in the proximal segment in 12 of 14 patients.…”
Section: Discussionmentioning
confidence: 99%
“…First, MB may cause coronary obstruction during systole. Intracoronary Doppler flow measurements have shown that the diastolic flow velocities are increased in MB segments, 3,27,35 and the peak systolic intracoronary pressure has been reported to be elevated within MB segments. 3,27,36 Intravascular ultrasonography has shown that the cross-sectional area in MB segments is reduced during systole and that this reduction continues into early diastole.…”
Section: Cardiac Events Associated With Myocardial Bridgingmentioning
confidence: 99%
“…14 The areas proximal to the bridge also appear prone to atherosclerotic lesions. 13,15,16 Our patient's angina was clinically refractory to medical therapy and he received an intracoronary stent. He developed two episodes of symptomatic restenosis necessitating CABG.…”
Section: Discussionmentioning
confidence: 92%